1964
DOI: 10.1111/j.1744-7348.1964.tb01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorous and carbamate insecticides as soil treatments for the control of wireworms

Abstract: SUMMARY Laboratory methods are described for testing soil insecticides against wireworms, and the results obtained with some organophosphorus and carbamate compounds tried as possible alternatives to chlorinated hydrocarbons are reported. The most promising compounds in the laboratory tests were thionazin, O‐ethyl S‐p‐tolylethylphosphonodithioate (Bayer 38156) and fenthion. These were tested in a small‐plot field trial with cereals, on land severely infested with wireworms: the compounds were applied to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Differences in susceptibilities between male and female P. vulgaris were greater than those for B. lampros probably because of the greater differences (P < 0-05) in weights of the sexes (Table II). The critical concentrations are within the dosage rates recommended for control of insect or nematode pests of agricultural crops, 2-8 lb/acre (2-24-8-96 kg/ha) and 8-32 lb/acre (8-96-35-84 kg/ha), respectively (Barker & Sasser, 1959;French, 1964;Griffiths & Bardner, 1964;Harrison, 1965;Howitt & Cole, 1962;Mulla, 1965;Shanks & Howitt, 1964;Steinhauer et ah, 1962;Suit & Feldman, 1961).…”
Section: Minimal Effective Dosage Of Thionazinmentioning
confidence: 78%
“…Differences in susceptibilities between male and female P. vulgaris were greater than those for B. lampros probably because of the greater differences (P < 0-05) in weights of the sexes (Table II). The critical concentrations are within the dosage rates recommended for control of insect or nematode pests of agricultural crops, 2-8 lb/acre (2-24-8-96 kg/ha) and 8-32 lb/acre (8-96-35-84 kg/ha), respectively (Barker & Sasser, 1959;French, 1964;Griffiths & Bardner, 1964;Harrison, 1965;Howitt & Cole, 1962;Mulla, 1965;Shanks & Howitt, 1964;Steinhauer et ah, 1962;Suit & Feldman, 1961).…”
Section: Minimal Effective Dosage Of Thionazinmentioning
confidence: 78%
“…Laboratory work investigating organophosphorus (OP) compounds as replacement soil insecticides for wireworm control suggested that the most promising compounds were thionazin and fenthion (Grif®ths & Bardner, 1964). Subsequent ®eld experiments on cereals (Grif®ths et al, 1967) and potato demonstrated that although the OP insecticides such as phorate (Caldicott & Isherwood, 1967;Edwards & Thompson, 1971) reduced wireworm populations, none were as effective as organochlorine compounds such as aldrin.…”
Section: Insecticidesmentioning
confidence: 99%